Geografía Organización del espacio mundial. Atlas geográfico y análisis de casos - BARROS, Claudia coord. (ESTRADA, 1999)
CONTENIDO :ALVARADO QUETGLES, RAQUEL; DOMINGUEZ ROCA, LUIS; GENTILE, ELVIRA; GONZALEZ, SILVIA G.; GUTIERREZ, ANDREA I.; PEDONE, CLAUDIA; ZUSMAN, PERLA